Cost effectiveness analysis (cea) of different recall methods for cervical cancer screening among women in Klang / Rima Marhayu Abdul Rashid - Rima Marhayu , Abdul Rashid (2015)
Cervical cancer screening in Malaysia is by opportunistic Pap smear which contributed to the low uptake of cervical screening. To overcome this, a pilot project called the SIPPS program (translated as information system of Pap smear program) had been introduced whereby women aged 20-65 years old were invited for Pap smear and recall in the following years to repeat the test if the previous cervical cytology was normal. This study aimed at determining which recall method is most cost-effective in getting women to repeat Pap smear. Methodology: A randomised control trial had been conducted at the health clinics of a suburban district that implemented the SIPPS program. One thousand women who had attended Pap smear and had normal cytology in the previous years were given a recall for repeat smear either by registered letter, phone messages, phone call and the usual postal letter. They were given eight weeks period to do Pap smear, failing which telephone calls were made by the researchers to find out why they did not respond to the recalls after the eight weeks period. The outcome chosen were the number of women that responded to the recall (defined by the women calling back, sending SMS or coming to the clinic after receiving the recall, irrespective of whether or not repeat Pap smear was done) and the number of uptake for repeat Pap smear (defined as the number of women who actually came to the clinics and do repeat smears). The total cost applied for cost-effectiveness analysis includes the cost of sending letter for first invitation, cost of the recall method and cost of twice vi Pap smear screening. Cost-effective analysis (CEA) of Pap smear uptake by each recall method was then performed. Results: The percentage of women who responded to recall by postal letters, registered letter, short message service (sms) and phone call were significantly different; 18.8%, 20.4%, 23.6% and 36.8%, respectively (p<0.05). The uptake of Pap smear by postal letter; registered letters, sms and phone calls were 18.8%, 20.0%, 21.6% and 34.4%, respectively (p<0.05). The total cost up to recall for a woman by each recall method were RM 25.91 (SD RM 0.03), RM 24.92 (SD RM 0.02), RM 24.74 (SD RM 0.06) and RM 23.71 (SD RM 0.03), for registered letter, postal letter, phone call and sms, respectively. The CER for the recall method was lowest by phone call compared to other interventions; RM 95.60 (SD RM 0.15) compared to RM 133.45 (SD RM 0.14), RM 153.23 (SD RM 0.15) and RM 156.23 (SD RM 0.11) for sms, registered letter and letter, respectively. ICER showed that it is most cost saving if the usual method of recall by postal letter be changed to recall by phone call. Conclusion: The possibility of letter as a recall for repeat Pap smear to reach the women is higher compared to sending SMS or making phone call. However, getting women to do repeat Pap smear is better with phone call which allows direct communication. Despite the high cost of phone call as a recall method for repeat Pap smear, it is the most cost-effective method compared to others.